S-Nitrosation of Glutathione Transferase P1-1 Is Controlled by the Conformation of a Dynamic Active Site Helix - Balchin, David (American Society for Biochemistry and Molecular Biology, 2013)
S-Nitrosation is a post-translational modification of protein cysteine residues, which occurs in response to cellular oxidative stress. Although it is increasingly being linked to physiologically important processes, the molecular basis for protein regulation by this modification remains poorly understood. We used transient kinetic methods to determine a minimal mechanism for spontaneous S-nitrosoglutathione (GSNO)-mediated transnitrosation of human glutathione transferase (GST) P1-1, a major detoxification enzyme and key regulator of cell proliferation. Cys(47) of GSTP1-1 is S-nitrosated in two steps, with the chemical step limited by a pre-equilibrium between the open and closed conformations of helix α2 at the active site. Cys(101), in contrast, is S-nitrosated in a single step but is subject to negative cooperativity due to steric hindrance at the dimer interface. Despite the presence of a GSNO binding site at the active site of GSTP1-1, isothermal titration calorimetry as well as nitrosation experiments using S-nitrosocysteine demonstrate that GSNO binding does not precede S-nitrosation of GSTP1-1. Kinetics experiments using the cellular reductant glutathione show that Cys(101)-NO is substantially more resistant to denitrosation than Cys(47)-NO, suggesting a potential role for Cys(101) in long term nitric oxide storage or transfer. These results constitute the first report of the molecular mechanism of spontaneous protein transnitrosation, providing insight into the post-translational control of GSTP1-1 as well as the process of protein transnitrosation in general.